Between vegetation and concrete: an analysis of urban forests in squares in the city of Castanhal, PA - Gonçalves, Larisse Medeiros; Santos, Luana Santos dos; Monteiro, Pedro Henrique da Silva; Rosal, Louise Ferreira (Paisagem e Ambiente, 2021)
Urban forest is important for sustainability and quality of life in a region, its implementation requires careful planning. This research aimed to diagnose, through a forest inventory, the urban forestry present in the squares of the city Castanhal, PA. An inventory of the arboreal vegetation was carried out from exsiccates. The absolute frequency and the relative frequency were calculated, classifying as native and exotic. We found 11 different species distributed in 8 botanical families, with 27.27% native to the country and 72.73% exotic, from Asia (75%), Central America (12.5%), and Africa (12.5%). Mangifera indica L. (34.7%) and Ficus benjamina L. (22.7%) presented a higher incidence, with more than 50% of the total species. It was concluded that the afforestation studied is below the established standards, requiring elements of functional native biodiversity key-words: Green areas. Urban Forests. Sustainability.